Equilibrium points in non-coalition n-person games - Vilkas, E. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Э. И. Вилкас. Ситуации равновесия в бескоалиционных играх многих лиц E. Vilkas. Nekoalicinių daugelio asmenų lošimų pusiausvyros situacijos